2018
DOI: 10.1016/j.bbamcr.2017.10.013
|View full text |Cite
|
Sign up to set email alerts
|

An easy-to-use FRET protein substrate to detect calpain cleavage in vitro and in vivo

Abstract: Calpain-1 and -2 are Ca-activated intracellular cysteine proteases that regulate a wide range of cellular functions through the cleavage of their protein substrates. Unlike degradative proteases, calpains make limited, transformative cleavages, typically in accessible sequences linking discrete subdomains, to irreversibly alter substrate functions. The biological roles of calpain and their interplay with calcium signaling are of significant biomedical interest as biomarkers and potential therapeutic targets in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 62 publications
1
2
0
Order By: Relevance
“…To this end, we analyzed the time course for the cleavage pattern of Sptan1 after treating the cells with 5 µM ionomycin, a potent activator of calcium ionophore and calpains. 39,40 We confirmed that 15 to 30 minutes of ionomycin treatments induced the cleavage of Sptan1 in the control cells, whereas such responses disappeared in Gnao1-deficient cells ( Figure 2D,E).…”
Section: Regulation Of Cytoskeletal Remodeling By Gα Osupporting
confidence: 67%
“…To this end, we analyzed the time course for the cleavage pattern of Sptan1 after treating the cells with 5 µM ionomycin, a potent activator of calcium ionophore and calpains. 39,40 We confirmed that 15 to 30 minutes of ionomycin treatments induced the cleavage of Sptan1 in the control cells, whereas such responses disappeared in Gnao1-deficient cells ( Figure 2D,E).…”
Section: Regulation Of Cytoskeletal Remodeling By Gα Osupporting
confidence: 67%
“…The Förster/fluorescence resonance energy transfer (FRET) technique has been applied for the detection of protease activity of conventional CAPNs, CAPN1 and CAPN2, to demonstrate real time proteolysis in vitro and in vivo (Bartoli et al, 2006;McCartney and Davies, 2019;McCartney et al, 2018a;Vanderklish et al, 2000). As for detection of activated CAPN3, our group has previously generated a prototype FRET-based sensor probe (SP) that is cleaved in in vitro test tubes by CAPN3 and CAPN3 splice variant lacking exons 6, 15 and 16 (Ono et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…The ability to cleave CCS was validated first by conjugating it to a fluorescence resonance energy transfer (FRET) dye pair (DABCYL and EDANS). [13][14][15] When mixed with calpain-1 and CaCl 2 in a bulk reaction, the CCS was cleaved, leading to a 2.5-fold increase in EDANS fluorescence over the control condition (Fig. S4A, ESI †).…”
mentioning
confidence: 99%